2020
DOI: 10.1128/iai.00886-19
|View full text |Cite
|
Sign up to set email alerts
|

Activation of ASC Inflammasome Driven by Toll-Like Receptor 4 Contributes to Host Immunity against Rickettsial Infection

Abstract: Rickettsiae are cytosolically replicating, obligately intracellular bacteria causing human infections worldwide with potentially fatal outcomes. We previously showed that Rickettsia australis activates ASC inflammasome in macrophages. In the present study, host susceptibility of ASC inflammasome-deficient mice to R. australis was significantly greater than that of C57BL/6 (B6) controls and was accompanied by increased rickettsial loads in various organs. Impaired host control of R. australis in vivo in ASC−/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 45 publications
5
27
0
Order By: Relevance
“…The copyright holder for this preprint this version posted September 8, 2021. ; https://doi.org/10.1101/2021.09.08.459437 doi: bioRxiv preprint and non-canonical inflammasome-dependent defense sensing, of which the former is in agreement with recent studies using R. australis (Rumfield et al, 2020). Thus, our data suggests that a dampening of both canonical and non-canonical inflammasomedependent signaling contributes to the enhanced survival and dissemination of pathogenic Rickettsia spp.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The copyright holder for this preprint this version posted September 8, 2021. ; https://doi.org/10.1101/2021.09.08.459437 doi: bioRxiv preprint and non-canonical inflammasome-dependent defense sensing, of which the former is in agreement with recent studies using R. australis (Rumfield et al, 2020). Thus, our data suggests that a dampening of both canonical and non-canonical inflammasomedependent signaling contributes to the enhanced survival and dissemination of pathogenic Rickettsia spp.…”
Section: Discussionsupporting
confidence: 90%
“…Recent findings further suggest that the intracytosolic survival of different Rickettsia spp. is either supported or suppressed by immune defense responses (e.g., IFN-I, TNF-α, or IL-1β) (Bechelli et al, 2018;Burke et al, 2020;Engström et al, 2019;Papp et al, 2016;Rumfield et al, 2020;Smalley et al, 2016), leaving the precise mechanism to be determined. Therefore, we first sought to evaluate the canonical and non-canonical inflammasome responses at the level of IL-1β and IL-1α cytokine secretion in the sera of R. typhi-, R. rickettsii-, and R. montanensis-infected animals.…”
Section: In Vivo Models Of Rickettsiosismentioning
confidence: 99%
See 1 more Smart Citation
“…These inflammatory cytokines upregulated by Atg5-dependent autophagy may contribute to reduced rickettsial loads in tissues of R. australisinfected Atg5-deficient macrophages (4). However, R. australis primarily targets microvascular endothelial cells in vivo while macrophages are the initial target cells at the cutaneous entry site of rickettsiae (3,59,60). It is not surprising to see a difference in cytokine profiles in R. australis-infected BMMs and sera of R. australis-infected Atg5-conditional knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…Although microvascular endothelial cells are the primary target of rickettsial infection (2), rickettsiae effectively invade macrophages and other types of cells, such as dendritic cells and hepatocytes. We, and others, have recently demonstrated that Rickettsia invades and survives in human macrophages, while macrophages play an important role in the pathogenesis of rickettsioses (3)(4)(5)(6)(7)(8)(9). However, it remains poorly understood how virulent rickettsiae utilize macrophages to develop a systemic infection in mammalian hosts.…”
Section: Introductionmentioning
confidence: 99%